A hard carbon material and preparation method thereof and application as negative electrode material for sodium ion batteries

The waste cotton fibers are modified through ball milling technology and one-step low-temperature carbonization treatment is adopted to solve the problems of high energy consumption and complex processes of high-temperature carbonization treatment in the existing technology, and hard carbon materials with high efficiency and stability are prepared, which realizes waste textiles High value utilization and excellent performance of sodium ion battery anode material.

CN118954484BActive Publication Date: 2025-01-10JIANGXI KEXING ENERGY STORAGE TECHNOLOGY CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411433021.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-15
Publication Date
2025-01-10
Estimated Expiration
2044-10-15

AI Technical Summary

Technical Problem

In the prior art, the preparation method for converting waste textiles into sodium ion battery hard carbon materials requires high temperature carbonization treatment, resulting in high energy consumption, high preparation cost, and complex process.

Method used

Ball mill technology is used to modify waste cotton fibers, and hard carbon materials are prepared through one-step low-temperature carbonization treatment, including shear powdering, ball milling pretreatment and low-temperature carbonization treatment, to obtain high-efficiency and stable hard carbon materials.

Benefits of technology

It has achieved the preparation of high-efficiency and good circulation stability with low cost and low energy consumption, which has reduced environmental pollution, improved the resource utilization value of waste textiles, and regulated the sodium storage performance of carbon materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118954484B_ABST
    Figure CN118954484B_ABST
Patent Text Reader

Abstract

The present invention belongs to the field of preparation of negative electrode materials for sodium ion batteries, and discloses a hard carbon material, a preparation method and an application as a negative electrode material for sodium ion batteries. The method comprises: shearing and pulverizing waste cotton cloth to obtain cotton cloth fragments; ball milling pretreatment of the cotton cloth fragments to obtain cotton fiber powder material; and carbonizing the cotton fiber powder material under an inert atmosphere to obtain a hard carbon material. The present invention modifies the structure of waste cotton fibers through ball milling technology, so that a hard carbon material with high first charge and discharge efficiency, good cycle stability and excellent rate discharge performance can be prepared through a one-step low-temperature carbonization treatment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of preparation of negative electrode materials for sodium ion batteries, and more specifically, relates to a hard carbon material and a preparation method thereof and application thereof as a negative electrode material for sodium ion batteries. Background Art

[0002] Sodium-ion batteries have received extensive attention in academia and the business community due to their low cost, excellent electrochemical performance, and high safety performance. Among them, carbon materials as sodium-ion negative electrode materials are considered to be the most promising negative electrode materials. Currently, biomass-based hard carbon materials prepared by carbonizing biomass materials (such as peanut shells, coconut shells, corn cobs, bamboo, etc.) have a lower voltage platform, higher reversible sodium storage capacity (>300mAh / g) and stable cycling ability.

[0003] Waste textiles are a type of waste resources generated in people's lives. According to statistics, China produces 20 million tons of waste textile materials each year, of which waste cotton fibers account for 20%. Converting waste textiles into energy materials is a strategy to make high-value use of waste textile resources. In recent years, the use of cotton fibers as biomass raw materials to prepare sodium ion battery negative electrode materials has also shown excellent sodium storage performance. This is due to the fact that cotton fibers are composed of pure cellulose and have a large number of pore structures for storing sodium after carbonization. However, in the process of biomass carbonization, it is necessary to carry out the carbonization at a higher temperature range (>1300°C), which will inevitably lead to high energy consumption and preparation costs. At present, there are related patent reports, such as: CN116705999A, which realizes the conversion of waste textiles into hard carbon materials for the negative electrode of sodium ion batteries by pretreatment, precarbonization and high-temperature carbonization methods. CN117985685A also treats mixed waste fibers, adopts melt coating and two-step carbonization treatment to obtain hard carbon negative electrode materials with excellent conductivity and good stability. However, these preparation methods require a two-step carbonization process, and carbon with excellent performance needs to be achieved at a higher carbonization temperature (>1300℃).

[0004] Therefore, in view of the complex pretreatment steps and high carbonization temperature of waste textiles (waste cotton fibers), it is urgent to propose a new method for preparing hard carbon materials, which can be used as a raw material for hard carbon negative electrodes of sodium ion batteries. Summary of the invention

[0005] The purpose of the present invention is to address the deficiencies of the prior art and to propose a hard carbon material and a preparation method thereof and an application thereof as a negative electrode material for sodium ion batteries. The present invention modifies the structure of waste cotton fibers by ball milling technology so that a hard carbon material with high first charge and discharge efficiency, good cycle stability and excellent rate discharge performance can be prepared by a one-step low-temperature carbonization treatment.

[0006] In order to achieve the above object, the first aspect of the present invention provides a method for preparing a hard carbon material, the method comprising the following steps:

[0007] S1: performing shearing and pulverizing treatment on the waste cotton cloth to obtain cotton cloth fragments;

[0008] S2: pre-treating the cotton cloth pieces by ball milling to obtain cotton fiber powder material;

[0009] S3: Under an inert atmosphere, the cotton fiber powder material is carbonized to obtain a hard carbon material (cotton fiber-based hard carbon material).

[0010] According to the present invention, preferably, the equipment used for the shearing and pulverizing treatment is a shearing machine.

[0011] According to the present invention, preferably, the size of the cotton cloth pieces is 0.5-1 cm 2 .

[0012] According to the present invention, preferably, the ball milling pretreatment is dry ball milling, and the operating conditions of the ball milling pretreatment include: the ball-to-material mass ratio is (10-1):1, the ball milling speed is 800-1500r / min, and the ball milling time is 10-120min.

[0013] According to the present invention, preferably, the ball milling time is 15-70 min.

[0014] According to the present invention, preferably, the rotation speed of the ball mill is 900-1500 r / min.

[0015] According to the present invention, preferably, the inert atmosphere is argon and / or nitrogen.

[0016] According to the present invention, preferably, the operating conditions of the carbonization treatment include: the temperature of the carbonization treatment is 650-950° C., the heating rate is 5-10° C. / min, and the time of the carbonization treatment is 1-6 h.

[0017] According to the present invention, preferably, the carbon yield of the carbonization treatment is 20-25%.

[0018] The second aspect of the present invention provides a hard carbon material prepared by the method for preparing the hard carbon material.

[0019] The third aspect of the present invention provides the use of the hard carbon material as a negative electrode material for a sodium ion battery.

[0020] In the present invention, as a preferred embodiment, the negative electrode material of the sodium ion battery includes a mixed binder of SBR (styrene-butadiene rubber) and CMC (carboxymethyl cellulose), conductive carbon black (Super P) and the hard carbon material of the present invention, and the mass ratio of the mixed binder of SBR and CMC (50% each), Super P and the hard carbon material of the present invention is 1:1:8; correspondingly, the preparation method of the negative electrode of the sodium ion battery includes: mixing the mixed binder of SBR and CMC, Super P and the hard carbon material of the present invention according to the mass ratio, grinding and slurrying (water is used as the medium), uniformly coating it on a copper foil, drying, slicing and standby use, so as to obtain the negative electrode of the sodium ion battery; further, metallic sodium is used as the counter electrode, the electrolyte is a 1.0M NaPF6 ethylene glycol dimethyl ether (DME) solution, and it is packaged with a 2032 button cell to obtain a sodium ion battery.

[0021] The beneficial effects of the technical solution of the present invention are as follows: the present invention uses ball milling technology to modify the structure of waste cotton fibers, so that hard carbon materials with high first charge and discharge efficiency, good cycle stability and excellent rate discharge performance can be prepared through a one-step low-temperature carbonization treatment. Specifically:

[0022] 1) The present invention uses low-cost waste cotton fiber as raw material

[0023] The present invention uses waste cotton fibers directly as raw materials for preparing hard carbon negative electrodes for sodium ion batteries, which can fully and reasonably utilize waste textile resources and reduce environmental pollution. On the other hand, it can realize the high value of waste textiles, turn waste into treasure, and generate significant economic benefits.

[0024] 2) The present invention uses ball milling technology to shorten the process flow and reduce energy consumption

[0025] In the present invention, the microstructure of the cotton fiber precursor is modified directly by ball milling technology, and the cotton fiber is converted from type I crystalline cellulose to type II amorphous fiber after ball milling. This structural transformation can increase the interlayer spacing of carbon atoms in the carbon material under low-temperature carbonization treatment, which is beneficial to improving the sodium storage capacity of the carbon material. The method of the present invention avoids the acid and alkali pretreatment and multiple carbonization strategies used in traditional methods, shortens the process flow, reduces production energy consumption, and is of great significance to the actual production of enterprises.

[0026] 3) The present invention can regulate the sodium storage performance of the hard carbon material of the present invention through ball milling process

[0027] In the present invention, the cotton fiber structure and surface pore characteristics can be changed by adjusting ball milling parameters, such as ball milling time and rotation speed, thereby affecting the sodium storage performance of the cotton fiber-based carbon material after carbonization, including the maximum reversible capacity, the first charge and discharge efficiency, the platform discharge capacity, the cycle stability, etc.

[0028] Other features and advantages of the present invention will be described in detail in the following detailed description. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] The above and other objects, features and advantages of the present invention will become more apparent through a more detailed description of exemplary embodiments of the present invention in conjunction with the accompanying drawings, wherein like reference numerals generally represent like components throughout the exemplary embodiments of the present invention.

[0030] Figure 1 An SEM picture of the cotton cloth pieces of Comparative Example 1 is shown.

[0031] Figure 2 The SEM image of the cotton fiber powder material after ball milling in Example 1 is shown.

[0032] Figure 3 The SEM image of the cotton fiber powder material after ball milling in Example 2 is shown.

[0033] Figure 4 The SEM image of the waste cotton fiber-based hard carbon material obtained in Comparative Example 1 is shown.

[0034] Figure 5 The SEM image of the waste cotton fiber-based hard carbon material obtained in Example 1 is shown.

[0035] Figure 6 The SEM image of the waste cotton fiber-based hard carbon material obtained in Example 2 is shown.

[0036] Figure 7 The XRD patterns of the cotton fiber powder materials after ball milling in Examples 1 and 2 and the XRD patterns of the cotton cloth fragments in Comparative Example 1 are shown ("Example 1" refers to Example 1, "Example 2" refers to Example 2, "Comparative 1" refers to Comparative Example 1, "Intensity" refers to intensity, and "2θ / degree" refers to angle, the same below).

[0037] Figure 8 The XRD patterns of the waste cotton fiber-based hard carbon materials obtained in Examples 1, 2 and Comparative Example 1 are shown.

[0038] Fig. 9 The charge and discharge curves (“Voltage” voltage, “Capacity” capacity, “Cycle” charge and discharge number, “ICE” first charge and discharge efficiency) of the sodium ion battery negative electrode obtained in Comparative Example 1 were performed three times at a current density of 0.05 A / g.

[0039] Fig.10 The charge and discharge curves of the sodium ion battery negative electrode obtained in Example 1 were performed three times at a current density of 0.05 A / g.

[0040] Fig.11 The charge and discharge curves of the sodium ion battery negative electrode obtained in Example 2 were obtained three times at a current density of 0.05 A / g.

[0041] Fig.12 The figure shows the rate performance ("Cycle Number" and "Coulombic efficiency") of the sodium ion batteries obtained in Examples 1 and 2 and Comparative Example 1 tested at different current densities.

[0042] Fig.13 The results of 100 cycle charge-discharge stability tests of the sodium ion batteries obtained in Examples 1 and 2 and Comparative Example 1 at a current density of 0.05 A / g are shown.

[0043] Fig.14 The results of long cycle stability tests of the sodium ion batteries obtained in Examples 1 and 2 and Comparative Example 1 at a current density of 2 A / g are shown. DETAILED DESCRIPTION

[0044] The preferred embodiments of the present invention will be described in more detail below. Although the preferred embodiments of the present invention are described below, it should be understood that the present invention can be implemented in various forms and should not be limited by the embodiments set forth herein. On the contrary, these embodiments are provided to make the present invention more thorough and complete, and to fully convey the scope of the present invention to those skilled in the art.

[0045] Example 1

[0046] This embodiment provides a method for preparing a hard carbon material, the method comprising the following steps:

[0047] S1: Weigh 5g of waste cotton fiber cloth and cut it into pieces with a shearing machine, the size of which is less than 1cm 2 ;

[0048] S2: dry ball milling the cotton cloth fragments, with a ball-to-material mass ratio of 5:1, a ball milling speed of 1400 r / min, and a ball milling time of 20 min to obtain a cotton fiber powder material;

[0049] S3: Place the cotton fiber powder material in a crucible and put it into a carbonization furnace protected by an argon atmosphere for carbonization treatment. The carbonization temperature is controlled to be 900° C. and the time is 2 hours to obtain a waste cotton fiber-based hard carbon material.

[0050] This embodiment also uses the obtained waste cotton fiber-based hard carbon material to prepare a sodium ion battery negative electrode and a sodium ion battery, and the preparation includes:

[0051] Waste cotton fiber-based hard carbon material, super P and binder are ground and mixed into slurry in a mass ratio of (8:1:1) (wherein: the solvent of the binder is water, and the solute is a 1% by mass SBR solution (obtained by diluting a 40% by mass solution) and a 1% by mass CMC powder).

[0052] After the slurry is evenly mixed, an appropriate amount of water can be added to adjust the slurry, and then the slurry is evenly coated on the copper foil current collector. After coating, the copper foil current collector coated with the slurry is dried in a vacuum oven at 100°C for 12 hours to obtain a negative electrode sheet; then the negative electrode sheet is sliced ​​with an electrode slicer, and then vacuum dried at 80°C for 3 hours after slicing to obtain a negative electrode for a sodium ion battery;

[0053] The sodium ion battery negative electrode is used as the working electrode, the sodium metal sheet is used as the counter electrode and the reference electrode, the electrolyte is a commercial sodium ion electrolyte (electrolyte composition: 1.0M NaPF6in DME=100 Vol%), and the glass fiber is used as the diaphragm; 2032 button cells are used for packaging to form a half-cell, and the assembly process is carried out in a glove box filled with argon to obtain a sodium ion battery.

[0054] Example 2

[0055] The difference between this embodiment and embodiment 1 is that the ball milling time is 45 minutes.

[0056] Example 3

[0057] The only difference between this embodiment and embodiment 2 is that the ball milling time is 60 min.

[0058] Example 4

[0059] The only difference between this embodiment and embodiment 2 is that the temperature of the carbonization treatment is 700°C.

[0060] Example 5

[0061] The only difference between this embodiment and embodiment 2 is that the temperature of the carbonization treatment is 800°C.

[0062] Example 6

[0063] The only difference between this embodiment and embodiment 2 is that the rotation speed of the ball mill is 1000 r / min.

[0064] Example 7

[0065] The only difference between this embodiment and embodiment 2 is that the rotation speed of the ball mill is 1200 r / min.

[0066] Example 8

[0067] The only difference between this embodiment and embodiment 2 is that the carbonization treatment time is 4 hours.

[0068] Comparative Example 1

[0069] The difference between this comparative example and Example 1 is that the cotton cloth pieces are directly subjected to the carbonization treatment of step S3.

[0070] Depend on Figure 1 It can be seen that the cotton fiber raw material is a long fiber structure with a diameter in the range of 20 microns. Figure 2 It can be seen that the cotton fiber powder material after ball milling in Example 1 has no obvious fiber structure. Figure 3 It can be seen that the cotton fiber powder material after ball milling in Example 2 becomes smaller blocks.

[0071] Depend on Figure 4 It can be seen that the sample of comparative example 1 still maintains the fiber structure after carbonization at 900°C, the fiber length is significantly shortened, and the diameter is also reduced to the range of 10 microns. Figure 5 It can be seen that the microstructure of the waste cotton fiber-based hard carbon material obtained in Example 1 is irregular block-shaped. Figure 6 It can be seen that the microstructure of the waste cotton fiber-based hard carbon material obtained in Example 2 has become smaller blocks.

[0072] Figure 7 The XRD patterns of the cotton fiber powder materials after ball milling in Examples 1 and 2 and the XRD pattern of the cotton cloth fragments in Comparative Example 1 are shown. Figure 7 It can be seen that: for Example 1, ball milling causes the cotton fiber to transform from crystal structure type I to amorphous crystal structure, and the characteristic peak intensity of type II is significantly increased; for Example 2, the amorphous peak intensity is higher and wider at II, indicating that the cotton fiber after ball milling has the amorphous characteristics of type II. Figure 7 It shows that the cotton fiber raw material has a crystalline structure dominated by cellulose type I.

[0073] Figure 8 The XRD patterns of the waste cotton fiber-based hard carbon materials obtained in Examples 1 and 2 and Comparative Example 1 are shown. Figure 8 It can be seen that for Example 1, the waste cotton fiber-based hard carbon material obtained by carbonization is an amorphous carbon material, and the peak angle at d002 (21.7 o ), compared with the sample obtained by carbonization in Example 1 (23.1 o ) is smaller, indicating that the interlayer distance of carbon atoms is increased. For Example 2, the d002 peak angle (21.5 o ) is smaller than that of Example 1, which proves that the interlayer spacing of its carbon atoms is larger. For Comparative Example 1, the sample obtained by carbonization is an amorphous carbon structure, and the interlayer spacing of its carbon atoms is about 0.385nm calculated based on the d002 position.

[0074] Depend on Fig. 9 It can be seen that the reversible capacity of the sodium ion battery negative electrode obtained in Comparative Example 1 can reach 170 mAh / g, and the first charge and discharge efficiency can reach 65%.

[0075] Depend on Fig.10 It can be seen that the reversible capacity of the sodium ion battery negative electrode obtained in Example 1 can reach 218.5 mAh / g, and the first charge and discharge efficiency can reach 75%.

[0076] Depend on Fig.11 It can be seen that the reversible capacity of the sodium ion battery negative electrode obtained in Example 2 can reach 272.3 mAh / g, and the first charge and discharge efficiency can reach 85.3%.

[0077] In addition, the results of the charge and discharge tests of other embodiments at a current density of 0.05A / g are as follows:

[0078] The reversible capacity of the sodium ion battery negative electrode obtained in Example 3 can reach 230.4 mAh / g, and the first charge and discharge efficiency can reach 80.3%;

[0079] The reversible capacity of the sodium ion battery negative electrode obtained in Example 4 can reach 201.4 mAh / g, and the first charge and discharge efficiency can reach 75%;

[0080] The reversible capacity of the sodium ion battery negative electrode obtained in Example 5 can reach 225.1 mAh / g, and the first charge and discharge efficiency can reach 80.3%;

[0081] The reversible capacity of the sodium ion battery negative electrode obtained in Example 6 can reach 190 mAh / g, and the first charge and discharge efficiency can reach 78%;

[0082] The reversible capacity of the sodium ion battery negative electrode obtained in Example 7 can reach 240 mAh / g, and the first charge and discharge efficiency can reach 82%;

[0083] The reversible capacity of the sodium ion battery negative electrode obtained in Example 8 can reach 250 mAh / g, and the first charge and discharge efficiency can reach 84%.

[0084] Fig.12 The rate performance of the sodium ion battery obtained in Example 1 tested at different current densities is shown. Fig.12 You can see:

[0085] The sodium ion battery obtained in Example 1 can maintain a reversible capacity of 183 mAh / g at a high current density of 2 A / g;

[0086] The sodium ion battery obtained in Example 2 can maintain a reversible capacity of 216 mAh / g at a high current density of 2 A / g;

[0087] The sodium ion battery obtained in Comparative Example 1 can maintain a reversible capacity of 101.6 mAh / g at a high current density of 2 A / g.

[0088] Fig.13 The results of the sodium ion battery obtained in Example 1 were tested for 100 cycles of charge and discharge stability at a current density of 0.05 A / g. Fig.13 You can see:

[0089] After 100 cycles, the sodium ion battery obtained in Example 1 has a reversible capacity of 212 mAh / g, which is 96.4% of the initial capacity;

[0090] After 100 cycles, the sodium ion battery obtained in Example 2 had a reversible capacity of 255.4 mAh / g, which was 93.8% of the initial capacity.

[0091] After 100 cycles, the sodium ion battery obtained in Comparative Example 1 had a reversible capacity of 133.5 mAh / g, which was 78.5% of the initial capacity.

[0092] In addition, the results of 100 cycle charge and discharge stability tests of other embodiments at a current density of 0.05A / g are as follows:

[0093] After 100 cycles, the capacity retention rate of the sodium ion battery obtained in Example 3 can reach 89.2%;

[0094] After 100 cycles, the capacity retention rate of the sodium ion battery obtained in Example 4 can reach 87.3%;

[0095] After 100 cycles, the capacity retention rate of the sodium ion battery obtained in Example 5 can reach 90.1%;

[0096] After 100 cycles, the capacity retention rate of the sodium ion battery obtained in Example 6 can reach 86.3%;

[0097] After 100 cycles, the capacity retention rate of the sodium ion battery obtained in Example 7 can reach 92.5%;

[0098] After 100 cycles, the capacity retention rate of the sodium ion battery obtained in Example 8 can reach 91.4%.

[0099] Fig.14 The results of the long cycle stability test of the sodium ion battery obtained in Example 1 at a current density of 2A / g are shown. Fig.14 It can be found that:

[0100] After 1200 cycles, the sodium ion battery obtained in Example 1 has a reversible capacity of 172 mAh / g and a capacity retention rate of 92.4%;

[0101] After 1200 cycles, the sodium ion battery obtained in Example 2 has a reversible capacity of 200 mAh / g and a capacity retention rate of 92.6%;

[0102] After 1200 cycles, the sodium ion battery obtained in Comparative Example 1 had a reversible capacity of 78 mAh / g and a capacity retention rate of 76.7%.

[0103] It can be seen that compared with Comparative Example 1, the performance of the sodium ion battery made using the waste cotton fiber-based hard carbon material of the present invention is significantly better than the performance of the battery made in Comparative Example 1 using cotton fiber carbon material that has not been ball-milled.

[0104] The embodiments of the present invention have been described above, and the above description is exemplary, not exhaustive, and is not limited to the disclosed embodiments. Many modifications and changes will be apparent to those skilled in the art without departing from the scope and spirit of the described embodiments.

Claims

1. A method for preparing a hard carbon material, characterized in that: The method comprises the following steps: S1: Shear and pulverize the waste cotton cloth to obtain cotton cloth fragments; the size of the cotton cloth fragments is 0.5-1 cm 2 ; S2: pre-treating the cotton cloth pieces by ball milling to obtain cotton fiber powder material; The ball milling pretreatment is dry ball milling, and the operating conditions of the ball milling pretreatment include: the ball-to-material mass ratio is (10-1): 1, the ball milling speed is 800-1500r / min, and the ball milling time is 15-70min; S3: Under an inert atmosphere, carbonizing the cotton fiber powder material to obtain a hard carbon material; The operating conditions of the carbonization treatment include: the carbonization treatment temperature is 650-950° C., the heating rate is 5-10° C. / min, and the carbonization treatment time is 1-6 hours.

2. The method for preparing a hard carbon material according to claim 1, wherein: The equipment used in the shearing and pulverizing process is a shearing machine.

3. The method for preparing a hard carbon material according to claim 1, wherein: The rotation speed of the ball mill is 900-1500r / min.

4. The method for preparing a hard carbon material according to claim 1, wherein: The inert atmosphere is argon and / or nitrogen.

5. The method for preparing a hard carbon material according to claim 1, wherein: The carbon yield of the carbonization process is 20-25%.

6. The hard carbon material prepared by the method for preparing a hard carbon material according to any one of claims 1 to 5.

7. Use of the hard carbon material according to claim 6 as a negative electrode material for sodium ion batteries.

Citation Information

Patent Citations

  • Preparation method of sodium ion battery hard carbon-based negative electrode material based on waste fabric recycling

    CN116705999A

  • Hard carbon material, preparation method and application thereof, and sodium ion battery negative electrode material

    CN117985685A